SOME ISSUES ON BANDITRY - Elizbarashvili, Zviad (European Scientific Journal, ESJ, 2012)
The article concerns the attempt of mixing the concept of â€œbanditryâ€ with the concept of â€œorganized crimeâ€ what is typical to the Anglo-American approach. The legislation of Georgia essentially differs from this approach as it exactly specifies different features of banditry and thus meets the requirements of the resolution of the Committee of Ministers of the European Council.